A preliminary study of the pressure and shear stress on a plane surface beneath a circular cylinder in turbulent flow fields (Journal of Naval Architecture and Marine Engineering, 2017)
This paper studies the fluctuating forces on a plane surface beneath a circular cylinder in the subcritical flow regime using two-dimensional computational fluid dynamics (CFD). The turbulent flow fields were calculated via numerical solutions of the NavierStokes (NS) equations without a turbulence model (laminar flow computation), large eddy simulation (LES), and Reynolds-Averaged N-S equations (RANS) approach with the shear-stress transport (SST) turbulence model. The primary goal is to evaluate the performance of 2-D turbulence simulation with different approaches and to have preliminary knowledge of the forces on the plane which is important in studying scours and flow-induced vibration in ocean engineering. Results show that although a coarse mesh scheme can only obtain potential flows, the laminar approach with high mesh resolution can adequately simulate turbulent flows at moderate Reynolds numbers. Spatially, the fluctuating forces on the plane surface due to the flow are significant within three times the cylinder diameter in the downstream, and within one cylinder diameter in the upstream of the cylinder. The pressure fluctuations are approximately two orders of magnitude larger than the shear stress fluctuations. In the frequency domain, the fluctuating forces are significant under twice the vortex-shedding frequency. Within one cylinder diameter in the downstream and upstream regions of the cylinder, the pressure fluctuations on the plane surface are well correlated, while the shear stress is not so well correlated.